Postablation Immune Microenvironment: Synergy between Interventional Oncology and Immuno-oncology - Kim, DaeHee; Erinjeri, Joseph P. (Seminars in Interventional Radiology, 2019)
Current tumor thermal ablation techniques rely on extreme temperatures to induce irreversible cellular injury and coagulative tissue necrosis. Ablation-induced cellular injury or death releases cancer neoantigens and activates the cancer-immunity cycle, potentially generating tumor-specific immune effectors. However, multiple negative regulatory modulators exist at each step of the cycle, mitigating meaningful and therapeutic anticancer effect provided by the immune system. Recent studies have focused on the introduction and testing of adjuvant immunotherapy combined with ablation to synergistically shift the equilibrium out of inhibitory immune modulation. This article reviews the immune microenvironment in relation to image-guided ablation techniques and discusses current and upcoming novel strategies to take advantage of antitumor immunity.
Keywords: immune microenvironment; ablation; interventional oncology; immunotherapy